Development of weft-knitted spacer fabrics with negative stiffness effect in a special range of compression displacement. Issue 16 (October 2015) - Chen, Fuxing; Hu, Hong; Liu, Yanping
Negative stiffness refers to a negative ratio of the force to the displacement in a deformed material system. It can be very useful in the design and fabrication of vibration isolation systems. In this study, a new kind of weft-knitted spacer structure that can achieve negative stiffness under compression was specially developed by using elastic yarn to knit the outer layers of spacer structure. Twelve fabric samples were knitted on an electronic flat knitting machine with three different linking distances and four diameters of spacer monofilaments. The compression tests were conducted to verify the negative stiffness effect of the fabrics after a steaming treatment. The results obtained have shown that the negative stiffness effect can be obtained for weft-knitted spacer fabrics in a special range of compression displacement if suitable fabric structure and fiber materials are used, and the decrease of the linking distance of spacer monofilaments can enhance the negative stiffness effect. It is expected that this study could provide useful information in the design and fabrication of spacer fabrics for vibration isolation.